Do governments tax agglomeration rents? - Hyun-Ju Koh; Nadine Riedel (Center for Economic Studies and ifo Institute (CESifo), 2010)
Using the German local business tax as a testing ground, we empirically investigate the impact of firm agglomeration on municipal tax setting behavior. The analysis exploits a rich data source on the population of German firms to construct detailed measures for the communities' agglomeration characteristics. The findings indicate that urbanization and localization economies exert a positive impact on the jurisdictional tax rate choice which confirms predictions of the theoretical New Economic Geography (NEG) literature. Further analysis suggests a qualification of the NEG argument by showing that a municipality's potential to tax agglomeration rents depends on its firm and industry agglomeration relative to neighboring communities. To account for potential endogeneity problems, our analysis exploits long-lagged population and infrastructure variables as instruments for the agglomeration measures.
Keywords: H73; R12; 330; agglomeration rents; corporate taxation; regional differentiation; Gemeindesteuer; Gewerbesteuer; Steuertarif; Agglomerationseffekt; Regionale Konzentration; Lokalisationseffekt; Deutschland